2012
DOI: 10.3109/00365599.2012.733961
|View full text |Cite
|
Sign up to set email alerts
|

Chronic asymptomatic inflammation of the prostate type IV and carcinoma of the prostate: Is there a correlation?

Abstract: No significant correlation between chronic prostatic inflammation and carcinoma of the prostate was detected. Contrary to expectations, a significantly higher score of inflammatory changes was found in BPH patients; also, total PSA levels were lower in the inflammation group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 23 publications
0
21
1
Order By: Relevance
“…Even though some of the literature has showed that CP/ CPPS is an important health issue in elder population, [25][26][27][28] the present study failed to observe such an association between CP/CPPS and previous colonoscopy in the elderly (≥60 years old). According to anatomical and physiological changes of the prostate in the elderly, a portion of the pathogenesis of prostate inflammation differs from that in young adults.…”
Section: Discussioncontrasting
confidence: 97%
See 1 more Smart Citation
“…Even though some of the literature has showed that CP/ CPPS is an important health issue in elder population, [25][26][27][28] the present study failed to observe such an association between CP/CPPS and previous colonoscopy in the elderly (≥60 years old). According to anatomical and physiological changes of the prostate in the elderly, a portion of the pathogenesis of prostate inflammation differs from that in young adults.…”
Section: Discussioncontrasting
confidence: 97%
“…We first excluded all subjects who had a history of CP/CPPS since the beginning of the NHI program in 1995. Thereafter, we selected 3933 controls matched with cases by age group (18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)30-39, 40-49, 50-59, 60-69, and >69 years) and index year. We selected the controls by matching them to a given CP/CPPS case simply due to use of medical services in the same index year of that particular case.…”
Section: Selection Of Cases and Controlsmentioning
confidence: 99%
“…Once again these findings, although not meaning causation, confirmed that there is inverse association between CII+ and PCA (4,(7)(8)(9)(10). The subject dealing with PCA associated with chronic inflammation has also been approached by other investigators, who, however, failed to detect any association (11)(12)(13). Our investigation is a single centre study including a large number of patients collected consecutively in an appropriate time of interval (24 months); also, biopsy specimens have been evaluated by a dedicated pathologist, who routinely reports the presence or absence of CII+ in each biopsy core.…”
Section: Discussionmentioning
confidence: 62%
“…8 In another study conducted in Scandinavia, frequency of CP in BPH was found 71%. 9 In another study conducted in Khatmandu the number was 15%. 10 Sciarra and collegues showed histological evidence of inflammation in approximately 40% of cases of BPH which is a significant risk factor for acute urinary retention.…”
Section: Discussionmentioning
confidence: 97%